Exploring structural and molecular diversity of Ericaceae hair root mycobionts: a comparison between Northern Bohemia and Argentine Patagonia - Vohník, Martin; Bruzone, M Clara; Knoblochová, Tereza; Fernández, Natalia V; Kolaříková, Zuzana; Větrovský, Tomáš; Fontenla, Sonia B (Mycorrhiza, 2023)
Core Ericaceae produce delicate hair roots with inflated rhizodermal cells that host plethora of fungal symbionts. These poorly known mycobionts include various endophytes, parasites, saprobes, and the ericoid mycorrhizal (ErM) fungi (ErMF) that form the ErM symbiosis crucial for the fitness of their hosts. Using microscopy and high-throughput sequencing, we investigated their structural and molecular diversity in 14 different host × site combinations in Northern Bohemia (Central Europe) and Argentine Patagonia (South America). While we found typical ericoid mycorrhiza in all combinations, we did not detect ectomycorrhiza and arbuscular mycorrhiza. Superficial mantles of various thickness formed by non-clamped hyphae were observed in all combinations except Calluna vulgaris from N. Bohemia. Some samples contained frequent intercellular hyphae while others possessed previously unreported intracellular haustoria-like structures linked with intracellular hyphal coils. The 711 detected fungal OTU were dominated by Ascomycota (563) and Basidiomycota (119), followed by four other phyla. Ascomycetes comprised Helotiales (255), Pleosporales (53), Chaetothyriales (42), and other 19 orders, while basidiomycetes Sebacinales (42), Agaricales (28), Auriculariales (7), and other 14 orders. While many dominant OTU from both hemispheres lacked close relatives in reference databases, many were very similar to identical to unnamed sequences from around the world. On the other hand, several significant ericaceous mycobionts were absent in our dataset, incl. Cairneyella, Gamarada, Kurtia, Lachnum, and Leohumicola. Most of the detected OTU could not be reliably linked to a particular trophic mode, and only two could be reliably assigned to the archetypal ErMF Hyaloscypha hepaticicola. Probable ErMF comprised Hyaloscypha variabilis and Oidiodendron maius, both detected only in N. Bohemia. Possible ErMF comprised sebacinoid fungi and several unnamed members of Hyaloscypha s. str. While H. hepaticicola was dominant only in C. vulgaris, this model ErM host lacked O. maius and sebacinoid mycobionts. Hyaloscypha hepaticicola was absent in two and very rare in six combinations from Patagonia. Nine OTU represented dark septate endophytes from the Phialocephala fortinii s. lat.-Acephala applanata species complex, including the most abundant OTU (the only detected in all combinations). Statistical analyses revealed marked differences between N. Bohemia and Patagonia, but also within Patagonia, due to the unique community detected in a Valdivian temperate rainforest. Our results show that the ericaceous hair roots may host diverse mycobionts with mostly unknown functions and indicate that many novel ErMF lineages await discovery. Transhemispheric differences (thousands of km) in their communities may be evenly matched by local differences (scales of km, m, and less).
Keywords: Endophytes; Helotiales; endofyty; symbióza; Sebacinales; Oidiodendron maius; Symbiosis; Ericaceae; Ascomycota; Central Europe; kořeny rostlin; Mycorrhizae; Root-associated fungi; Fungal root endophytes; Hyaloscypha sp.; South America; Ericoid mycorrhizal fungi; Plant Roots; mykorhiza; Basidiomycota